Impacts of the COVID-19 pandemic on diagnosis, treatment and mortality of patients with Head and Neck Cancer - Silva, Caroline Reis; Almeida, Ianca Lopes Macedo de Oliveira; Souza, Iasmim Dantas de; Ferreira, Lays Araújo; Monteiro, Rhayane da Conceição; Pires, Alessandra Laís Pinho Valente; Cerqueira, Joana Dourado Martins (Research, Society and Development, 2024)
Introduction: The COVID-19 pandemic has spread worldwide, causing a collapse in health services. Among the affected systems were the services for the treatment of Head and Neck Cancer, which, in view of the sanitary measures of social isolation, had their routine care, diagnoses and treatment postponed. Consequently, these factors may have result in an unfavorable prognosis, compromising the survival of these cancer patients. Objective: Conduct a literature review on the impacts of the COVID-19 pandemic on diagnosis, treatment and mortality of patients with Head and Neck Cancer. Method: This study was carried out from the search for articles in two bibliographic databases - PubMed and SciELO, published in the last two years, in Portuguese and English. Using the combination of the descriptors “Impact of COVID-19”, “diagnosis”, “treatment”, “mortality”, “Cancer of head and neck” and their respective in English, associated through Boolean operators “AND” and “OR”. Results: Initially, 220 articles were found and after establishing the inclusion and exclusion criteria, 13 articles were included for the qualitative analysis. Final considerations: This study concludes that the difficulty of access to specialized centers, the incentive to isolation and the restriction of personal contact, added to socioeconomic aspects in the period of the COVID-19 pandemic, directly impacted the diagnosis and treatment of Head and Neck Cancer.